Михайло Злобинець: бандурист та просвітник - Силка, О.; Синявська, Л. (Краєзнавство, 2017)
У статті на основі широкого фактологічного матеріалу висвітлено основні віхи життя та громадсько-просвітницької діяльності українського бандуриста, учителя, очільника просвітницького руху на Золотоніщині (суч. Черкаська область) Михайла Олександровича Злобинця (літературний псевдонім–Домонтович). Закцентовано увагу на різносторонніх аспектах його діяльності: організація студентського ансамблю бандуристів у Києві на початку ХХ ст., видання україномовних книг, створення та очолення Осередку «Просвіти» у м. Золотоноша, участь в українському Червонохрестному русі тощо. The article is based on extensive factual material covers the major milestones of life and public educational activities of Ukrainian bandura, teacher, leader of the movement for educational Zolotonischyni (modern. Cherkasy region) Mikhail Alexandrovich Zlobyntsya (pen name – Domontovych). The attention is paid to diverse aspects of its activities: organization of student Bandura Ensemble of Kiev in the early twentieth century, publishing Ukrainian books, creating and leading Branch “Prosvita” in Zolotonosha, participation in Ukrainian Red Cross movement and so on. Indicated that the name Michael Zlobyntsya named one of the Zolotonosha streets (Cherkasy region). His poem “Wake up father, you should not sleep...” translated into Russian and English. Proved that the life, personal beliefs and legacy of Mikhail Alexandrovich Zlobyntsya is part of a large-scale public cultural and educational movement Naddniprianshchyna.Raising on the surface partially forgotten layer of displays of public initiatives in the area of creation associations of cultural and educational local focus is feasible contribution to the writing of a new, objective history of towns and villages in Ukraine. Research of personal participation of citizens in such processes allows derived from historical oblivion generation of those, whose personal beliefs were formed during the Russian Revolution in 1905, active work took place in the 10 – 20-ies and forced silence occurred in the 30-ies XX century. В статье на основе широкого фактологического материала освещены основные этапы жизни и общественно-просветительской деятельности украинского бандуриста, учителя, лидера общественных организаций на Золотонощине (совр. Черкасская обл.) Михаила Александровича Злобинца (литературный пвсендоним – Домонтович). Акцентировано внимание на разностронних аспектах его деятельности: организация студенческого ансамбля бандуристов в Киеве в начале ХХ в., издание украиноязычных книг, организация и возглавление местной культурно-образовательной организации «Просвита» в г. Золотоноша, участие в общественной организации Украинский Красный Крест.